An update on angiotensin-converting enzyme 2 structure/functions, polymorphism, and duplicitous nature in the pathophysiology of coronavirus disease 2019: Implications for vascular and coagulation disease associated with severe acute respiratory syndrome coronavirus infection - Devaux, Christian A.; Camoin-Jau, Laurence (Frontiers in Microbiology, 2022)
It has been known for many years that the angiotensin-converting enzyme 2 (ACE2) is a cell surface enzyme involved in the regulation of blood pressure. More recently, it was proven that the severe acute respiratory syndrome coronavirus (SARS-CoV-2) interacts with ACE2 to enter susceptible human cells. This functional duality of ACE2 tends to explain why this molecule plays such an important role in the clinical manifestations of coronavirus disease 2019 (COVID-19). At the very start of the pandemic, a publication from our Institute (entitled “ACE2 receptor polymorphism: susceptibility to SARS-CoV-2, hypertension, multi-organ failure, and COVID-19 disease outcome”), was one of the first reviews linking COVID-19 to the duplicitous nature of ACE2. However, even given that COVID-19 pathophysiology may be driven by an imbalance in the renin-angiotensin system (RAS), we were still far from understanding the complexity of the mechanisms which are controlled by ACE2 in different cell types. To gain insight into the physiopathology of SARS-CoV-2 infection, it is essential to consider the polymorphism and expression levels of the ACE2 gene (including its alternative isoforms). Over the past 2 years, an impressive amount of new results have come to shed light on the role of ACE2 in the pathophysiology of COVID-19, requiring us to update our analysis. Genetic linkage studies have been reported that highlight a relationship between ACE2 genetic variants and the risk of developing hypertension. Currently, many research efforts are being undertaken to understand the links between ACE2 polymorphism and the severity of COVID-19. In this review, we update the state of knowledge on the polymorphism of ACE2 and its consequences on the susceptibility of individuals to SARS-CoV-2. We also discuss the link between the increase of angiotensin II levels among SARS-CoV-2-infected patients and the development of a cytokine storm associated microvascular injury and obstructive thrombo-inflammatory syndrome, which represent the primary causes of severe forms of COVID-19 and lethality. Finally, we summarize the therapeutic strategies aimed at preventing the severe forms of COVID-19 that target ACE2. Changing paradigms may help improve patients’ therapy.